Memperkuat Benteng Keuangan: Optimalisasi Sistem Pengendalian Internal - Anggerwati, A Indah; Hermin, Hermin; Ernawati, Ernawati; Asia, Nur (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This study aims to analyze the internal control system (SPI) implementation at the Polkes Kodam Makassar. This research uses a qualitative approach with a phenomenological design focusing on understanding the experiences, views, and perceptions of individuals related to the implementation of SPI in financial management. Participants in this study consisted of financial management officials, administrative staff, and other related parties who were directly involved in financial management at the Polkes Kodam Makassar. Data were collected through in-depth interviews and direct observation of the occurring processes. The results showed that the implementation of SPI at Polkes Kodam Makassar has met most of the standards set by the government, including safeguarding assets, accuracy of financial reports, and compliance with regulations. Nonetheless, the main challenge faced is that internal supervision has not been fully optimized, which has the potential to cause budget deviations. In addition, while financial information is readily available, the system for disseminating and understanding such information needs to be improved to make it more transparent and easily understood by all relevant parties. Improvements in these two aspects will strengthen accountability, transparency, and efficiency in the financial management of Polkes Kodam Makassar